ANALISIS ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG), CORPORATE CASH HOLDINGS, DAN NILAI PERUSAHAAN - Carmenita, Bernadette; Handoko, Jesica; Mokoginta, Dirgantara Dahana (Jurnal Aplikasi Akuntansi, 2025)
Implementing environmental, social, and governance (ESG) activities is considered a consideration for current investments because ESG proves a company's responsibility to investors and the social environment. The application of ESG is thought to produce useful scores for investors and influence company value either directly or mediated by Corporate Cash Holdings (CCH). In contrast, with ESG, CCH can be controlled and create company legitimacy. This research is a quantitative study that examines the influence of ESG and CCH on company value as well as the influence of ESG on company value, with CCH as a mediator. The research objects used are non-financial sector companies listed on the IDX and divided into manufacturing and non-manufacturing sectors in the 2020-2022 period—the analysis technique uses multiple linear regression analysis methods and the Sobel test. The research results show that ESG has a significant influence on company value. Regarding the CCH variable, the results show a negative but significant effect on company value, while ESG has a positive and significant impact on company value through CCH as mediation.